Does health-oriented training improve cardiovascular parameters of smoking women? - Szmyt, Agnieszka; Podgórski, Tomasz; Szmyt, Grażyna; Clark, Cain C.T.; Górny, Mirosław Paweł; Gronek, Piotr (Akademia Wychowania Fizycznego w Poznaniu)
Nicotine addiction is a serious medical and societal problem; making smoking cigarettes one of the most prevalent contributors to premature death, globally, and any avenue to facilitate smoking cessation is of vital importance. The aim of this study was to investigate the effect of 6-week health-oriented and/or concentration training programme on cardiovascular parameters and aerobic capacity in 118 young female smokers. This study found that combined health-oriented and concentration training resulted in greater improvements in VO2max and blood pressure, as compared to concentration training alone; whilst resting values of heart rate (HR) decreased significantly after a 6-week process of aerobic and concentration training. Exercise and concentration training positively influenced smoking cessation and cardiovascular parameters in young females.
Keywords: smoking cessation; aerobic training; concentration training; cardiovascular parameters